Involvement of dual‐strand of the miR‐144 duplex and their targets in the pathogenesis of lung squamous cell carcinoma. Issue 1 (6th December 2018) - Uchida, Akifumi; Seki, Naohiko; Mizuno, Keiko; Misono, Shunsuke; Yamada, Yasutaka; Kikkawa, Naoko; Sanada, Hiroki; Kumamoto, Tomohiro; Suetsugu, Takayuki; Inoue, Hiromasa
Abstract : The prognosis of patients with advanced‐stage lung squamous cell carcinoma (LUSQ) is poor, and effective treatment protocols are limited. Our continuous analyses of antitumor microRNAs (miRNAs) and their oncogenic targets have revealed novel oncogenic pathways in LUSQ. Analyses of our original miRNA expression signatures indicated that both strands of miR‐144 ( miR‐144‐5p, the passenger strand; miR‐144‐3p, the guide strand) showed decreased expression in cancer tissues. Additionally, low expression of miR‐144‐5p significantly predicted a poor prognosis in patients with LUSQ by The Cancer Genome Atlas database analyses (overall survival, P = 0 .026; disease‐free survival, P = 0 .023). Functional assays revealed that ectopic expression of miR‐144‐5p and miR‐144‐3p significantly blocked the malignant abilities of LUSQ cells, eg, cancer cell proliferation, migration, and invasion. In LUSQ cells, 13 and 15 genes were identified as possible oncogenic targets that might be regulated by miR‐144‐5p and miR‐144‐3p, respectively. Among these targets, we identified 3 genes ( SLC44A5, MARCKS, and NCS1 ) that might be regulated by both strands of miR‐144 . Interestingly, high expression of NCS1 predicted a significantly poorer prognosis in patients with LUSQ (overall survival, P = 0 .013; disease‐free survival, P = 0 .048). By multivariate analysis, NCS1 expression was found to be an independent prognostic factor for patients with LUSQ patients. Overexpression of NCS1 was detected in LUSQ clinical specimens, and its aberrant expression enhanced malignant transformation of LUSQ cells. Our approach, involving identification of antitumor miRNAs and their targets, will contribute to improving our understanding of the molecular pathogenesis of LUSQ. Abstract : Both strands of of miR‐144‐5p (the passenger strand) and miR‐144‐3p (the guide strand) acted as antitumor miRNAs in lung squamous cell carcinoma (LUSQ) cell lines. Low expression of miR‐144‐5p significantly predicted poor prognoses of patients with LUSQ (OS: P = 0.026, DFS: P = 0.023). Neuronal calcium sensor 1 (NCS1) was directly regulated by both miR‐144‐5p and miR‐144‐3p in LUSQ cells and aberrant expression of NCS1 was detected in LUSQ clinical specimens.